Motivasi Orang Tua Dalam Memilih Sekolah di SDIT Banten Islamic School Kramatwatu Serang Banten - Putra, Arta Rusidarma; Silfiana, Silfiana (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This study aims to describe the intrinsic motivational factors of parents choosing an integrated Islamic school, describe the extrinsic motivational factors of parents choosing an integrated Islamic school, and describe the expectations of parents after their child graduates from the integrated Islamic school Banten Islamic School. This study uses a descriptive qualitative method with a phenomenological design. Collecting data by interview, observation, and documentation. The validity of the data using triangulation. Data analysis with reduction, display, and conclusion. The results of the study revealed that the factors motivating parents to choose Banten Islamic School Integrated Islamic Elementary School consisted of extrinsic and intrinsic factors. extrinsic motivational factors motivated parents include school location and environment, physical facilities, vision and mission, portion of religious education, educator profiles, learning curriculum, alternative activities, school order and cleanliness, costs, scholastic skills, alumni achievements and success. While the intrinsic motivation factors, including the desire for children to be pious and pious, mastering general and religious knowledge, children to be independent, brave and responsible, achievers. While the hope of parents after their children graduate is to become pious and pious children and to be responsible for themselves and others